2008
DOI: 10.1158/1078-0432.ccr-08-1032
|View full text |Cite
|
Sign up to set email alerts
|

Improving Gemcitabine-Mediated Radiosensitization Using Molecularly Targeted Therapy: A Review

Abstract: In the last three decades, gemcitabine has progressed from the status of a laboratory cytotoxic drug to a standard clinical chemotherapeutic agent and a potent radiation sensitizer. In an effort to improve the efficacy of gemcitabine, additional chemotherapeutic agents have been combined with gemcitabine (both with and without radiation) but with toxicity proving to be a major limitation. Therefore, the integration of molecularly targeted agents, which potentially produce less toxicity than standard chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 88 publications
(103 reference statements)
1
40
0
Order By: Relevance
“…Statins have been shown to 17 reduce NFB activation by inhibiting prenylation [36][37] and our data show that in Capan-2 cells NFB was reduced. In the same time phosphorylation of Raf and MEK were affected, which can be explained by an inhibited prenylation of Ras [32][33][34][35][36][37][38][39][40][41]. The reason why Panc-1 and MIA PaCa-2 cells were less sensitive to these effects remains to be studied.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Statins have been shown to 17 reduce NFB activation by inhibiting prenylation [36][37] and our data show that in Capan-2 cells NFB was reduced. In the same time phosphorylation of Raf and MEK were affected, which can be explained by an inhibited prenylation of Ras [32][33][34][35][36][37][38][39][40][41]. The reason why Panc-1 and MIA PaCa-2 cells were less sensitive to these effects remains to be studied.…”
Section: Discussionmentioning
confidence: 52%
“…Gemcitabine is the current standard chemotherapeutic drug for treatment of pancreatic cancer but with minor benefit [37]. However, we found that in combination treatment, show that silencing of P2X7 with siRNA prevented the effect of atorvastatin on cell proliferation.…”
Section: Discussionmentioning
confidence: 65%
“…The rationale behind the latter approach is based on the knowledge that gemcitabine activates checkpoint kinases, which regulate the cell cycle progression. Preclinical studies using selective knockout of checkpoint kinase 1 in pancreas tumor cell lines confirmed the theoretical background [71]. With EGFR inhibitors, the research has advanced much further.…”
Section: Discussionmentioning
confidence: 81%
“…For more than a decade, gemcitabine has been used for the treatment of metastatic pancreatic cancer [14]. Recent clinical studies have shown favorable therapeutic responses and toxicity profiles of gemcitabine treatment in patients with advanced HNSCC [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical studies have shown favorable therapeutic responses and toxicity profiles of gemcitabine treatment in patients with advanced HNSCC [15,16]. Gemcitabine increases tumor cell sensitivity to radiation-induced apoptosis and hence is used as a radiation sensitizer in solid malignancies [14,17,18]. Antitumor activity of gemcitabine is mediated by multiple mechanisms dependent upon tumor types [19][20][21].…”
Section: Introductionmentioning
confidence: 99%